Deregulasi Dan Debirokrasi Pelayanan Publik: Strategi Dan Langkah Untuk Meningkatkan Mutu Pelayanan Publik Di Kabupaten / Kota - Sutardji Sutardji (FISIP UWP, 2010)
This paper discusses the need for deregulation and debureaucratization to improve the quality of public services. Deregulation and debureaucratization in public service, which is basically a part of the public administration reform is needed to improve the performance of bureaucracy to be more effective, efficient and competitive. So that will be spurred to further enhance community participation and initiative in the process of national and regional development. In this paper offers two strategies, namely